2019
DOI: 10.1155/2019/8479076
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Hemoglobin Level of Complicated and Uncomplicated Malaria Cases among Children: A Cross-Sectional Study in Kumasi Metropolis, Ghana

Abstract: Introduction. Malaria is a leading cause of mortality among children below 5 years in Ghana. Its parasites are known to cause the degradation of hemoglobin, resulting in the production of reactive oxygen species and hence oxidant stress. Therefore, this study was carried out to compare the levels of oxidative stress between children with complicated and uncomplicated malaria infection in Kumasi, Ghana. Method. Subjects were recruited from hospitals in the Kumasi Metropolis. This was a cross-sectional study, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Malaria is one of the most common infectious diseases in the world and one of the greatest global public health problems [ 1 ], mostly among children under 5 years [ 2 ]. About 90% of the world's severe and fatal malaria is projected to affect young children in sub-Saharan Africa [ 3 ], as major complications of severe falciparum malaria (SFM) develop rapidly and progress to death within hours or days [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria is one of the most common infectious diseases in the world and one of the greatest global public health problems [ 1 ], mostly among children under 5 years [ 2 ]. About 90% of the world's severe and fatal malaria is projected to affect young children in sub-Saharan Africa [ 3 ], as major complications of severe falciparum malaria (SFM) develop rapidly and progress to death within hours or days [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is considered a determinant of disease severity during P. falciparum malaria infection and increases during disease progression [ 21 23 ]. Malaria-associated AKI has been proposed as a consequence of parasite adhesion and an exacerbated immune response against the products of oxidative stress released during Plasmodium infection [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a release of biomarkers of oxidative stress such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) via host-parasite interaction. This ultimately stimulates the immune system with the possibility of causing red cell destruction through the induction of oxidative damages [12]. Therefore, red blood cells infected with plasmodium parasite are under constant oxidative stress utilized by the parasite with a resultant rise in antioxidant levels in the blood [12].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies suggested that oxidative stress during malaria plays a protective role, others opposed that it plays a deleterious role by worsening the pathological outcome of the infection [12]. In malaria, oxidative stressors levels such as malondialdehyde (MDA) and superoxide (SOD) are higher while catalase levels are lower [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation